2014
DOI: 10.1097/md.0000000000000078
|View full text |Cite
|
Sign up to set email alerts
|

Truview EVO2 and Standard Macintosh Laryngoscope for Tracheal Intubation During Cardiopulmonary Resuscitation

Abstract: The aim of this study was to compare the performance of the Truview EVO2 laryngoscope in manikin-simulated cardiopulmonary resuscitation (CPR) and no-CPR scenarios with standard intubation technique.Participants performed 4 scenarios in random order: endotracheal intubation (ETI) using Macintosh laryngoscope (MCL), Truview EVO2 laryngoscope in no-CPR patient scenario, and intubation during uninterrupted chest compressions using both laryngoscopes. The participants were directed to make 3 attempts in each scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
2
5
0
1
Order By: Relevance
“…One study was congruent with ours regarding increased number of 9 attempts with truview but other studies found more number of 10,[20][21][22]26 attempts with macintosh and equal number of attempts in both 12,13,16,19,25 groups. Increase number of attempts required for intubation in Truview Evo2 laryngoscope was may be due to relative inexperience with the newer device.…”
Section: Discussionsupporting
confidence: 80%
“…One study was congruent with ours regarding increased number of 9 attempts with truview but other studies found more number of 10,[20][21][22]26 attempts with macintosh and equal number of attempts in both 12,13,16,19,25 groups. Increase number of attempts required for intubation in Truview Evo2 laryngoscope was may be due to relative inexperience with the newer device.…”
Section: Discussionsupporting
confidence: 80%
“…The average time of intubation [12]. In the study by Gaszyńska et al, the MAC intubation time was 16.6 s, while the first attempt efficiency equalled 73.3% [14]. However, in another study Gaszyńska obtained a first attempt effectiveness of 53.3% and a total effectiveness of 80% [31].…”
Section: Discussionmentioning
confidence: 93%
“…Gaszyńska et al, in a group of 30 paramedics, noted that the necessary time to perform intubation with the MAC In cases of intubation with EVO2, the nurses were able to achieve a first attempt effectiveness of 68.8% and an overall efficiency of 87.2% within 35.5 s (IQR, 27-36.5 s). In the study by Gaszyńska et al, the efficacy of the first intubation attempt was 63.3%, with a total efficiency of 90% and a median duration of 28.64 s (24.02-38.34 s) [14]. Singh showed an 88% effectiveness of EVO2 intubation performed in 28.6 s [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Do badania zakwalifikowano 58 studentów ostatniego roku ratownictwa medycznego. Badania innych autorów wskazują, że w celu porównania skuteczności różnych metod intubacji wystarczająca jest 30-osobowa grupa badawcza [7,8]. Badanie zostało przeprowadzone w marcu 2015 r.…”
Section: Materiał I Metodyunclassified